2015
DOI: 10.1152/ajpheart.00338.2015
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training-induced changes in serum adropin level are associated with reduced arterial stiffness in middle-aged and older adults

Abstract: Fujie S, Hasegawa N, Sato K, Fujita S, Sanada K, Hamaoka T, Iemitsu M. Aerobic exercise training-induced changes in serum adropin level are associated with reduced arterial stiffness in middle-aged and older adults. Am J Physiol Heart Circ Physiol 309: H1642-H1647, 2015. First published September 14, 2015; doi:10.1152/ajpheart.00338.2015.-Aging-induced arterial stiffening is reduced by aerobic exercise training, and elevated production of nitric oxide (NO) participates in this effect. Adropin is a regulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 35 publications
(50 reference statements)
2
53
3
2
Order By: Relevance
“…Moreover, increased levels of adropin are associated with elevated NOx levels and reduced arterial stiffness. Thus, it is possible that adropin may promote arterial stiffness via NO-dependent signaling [53]. In line with this data, physical exercise upregulates circulating adropin in humans, which is accompanied by improved endothelial function [54].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, increased levels of adropin are associated with elevated NOx levels and reduced arterial stiffness. Thus, it is possible that adropin may promote arterial stiffness via NO-dependent signaling [53]. In line with this data, physical exercise upregulates circulating adropin in humans, which is accompanied by improved endothelial function [54].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 54%
“…Similarly, it was found that adropin enhances insulin signaling and promotes glucose oxidation in mice fed a high-fat diet, which is associated with higher cardiac output [52]. Adropin levels are high after the aerobic exercise-training in humans [53]. Moreover, increased levels of adropin are associated with elevated NOx levels and reduced arterial stiffness.…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 96%
“…Circulating adropin concentrations have been measured in several mammalian species using commercially produced enzyme immunoassays (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Human studies have screened for associations between plasma adropin concentrations and cardiovascular disease (5,8,12,17), endothelial function (10,11), type 2 diabetes (T2D) (7,9,14,17), obesity and aging (6), and exercise response (23).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic training decreases arterial stiffness, (1)(2)(3) an independent risk factor for cardiovascular disease, (4) possibly due to an increase in basal nitric oxide (NO) production. (5)(6)(7)(8) High-intensity resistance training increases arterial stiffness, but low-intensity resistance training seems to have no unfavorable effects on arterial stiffness. (2,9) Combined aerobic and resistance exercise training is often recommended in clinical practice.…”
mentioning
confidence: 99%